A comprehensive study on surface integrity of nickel-based superalloy Inconel 718 under robotic belt grinding. Issue 1 (2nd January 2019) - Wang, Junwei; Xu, Jijin; Wang, Xiangfei; Zhang, Xiaoqiang; Song, Xuefeng; Chen, Xiaoqi
ABSTRACT: Surface integrity of materials should be considered under robotic belt grinding in order to achieve desired finishing quality. In this work, the surface integrity of nickel-based superalloy Inconel 718, involving morphological structure, surface roughness, residual stress and structural domain size, was characterized systematically. A novel predicted model of grinding parameters optimization was proposed based on linear weighting function. The result shows that considerable compressive stress (about−355 MPa) and minimum roughness on material surface are achieved simultaneously at the grinding force of 178 kPa and belt speed of 31 m/s. The morphological structures and microhardness for the specimen under the optimized condition were further analyzed and discussed. Surface hardness is increased by 15%. Grain refinement and a large number of dislocations occur in the subsurface, which are attributed to continuous partial dynamic recrystallization associated with combined effects of plastic deformation and thermal treatment, which results from grinding force and belt speed. The new findings are of significance for ensuring surface integrity with optimal process parameters.